Biomechanics of world-class 800 m women at the 2017 IAAF World Championships - Hanley, B.; Merlino, S.; Bissas, A. (Frontiers in Sports and Active Living, 2022)
The 800 m race challenges the aerobic and anaerobic energy systems, and athletes adopt a technique that allows for running efficiency as well as sprinting speeds. The aim of this novel study was to compare important kinematic variables between the two laps of the 2017 IAAF World Championships women's final. Video data (150 Hz) were collected of all eight finalists on both laps at a distance approximately 50 m from the finish line along the home straight. Running speed, step length, cadence, temporal variables, sagittal plane joint angles, and shank angle at initial contact were measured. Running speed was faster on lap 2 (p = 0.008) because of large increases in cadence (p = 0.012). These higher cadences resulted in large decreases in contact times (p = 0.031) and in flight times (p = 0.016) on lap 2. Greater knee flexion and ankle plantarflexion (p = 0.039) at initial contact on lap 2 seemed partly responsible for shorter swing times (p = 0.016), and which accompanied a decrease in shank angle at initial contact from lap 1 (7°) to a more vertical position on lap 2 (4°) (p = 0.008). Coaches should note that the need for higher cadence, horizontal impulse production during shorter contact times, and the adoption of forefoot striking require strength and neural system training to allow for athletes to increase cadence during the sprint finish. Increasing cadence (and not step length) was the driving factor for faster finishing speeds in the women's 800 m.